Clinical Significance of Detection of Coagulation Indexes, Immune Factors and Inflammatory Factors in Patients with Pregnancy-Induced Hypertension Syndrome in China - Fengmei SHI; Aijun YU; Limei YUAN (Tehran University of Medical Sciences, 2019)
Background: To investigate the clinical significance of monitoring the coagulation indexes, immune factors and inflammatory factors in pregnancy-induced hypertension syndrome (PIH). Methods: 90 pregnant women with PIH admitted in Weihaiwei People's Hospital of Shandong Province, China from 2016 to 2017 were collected, including 45 cases in mild-moderate group and 45 cases in severe group. Another 45 normal pregnant women at the same period were selected as control group. The immune indexes, four index signs of coagulation bloods and serum inflammatory factors in three groups of subjects were determined. Results: The levels of complement 3 (C3), complement 4 (C4), immunoglobulin A (IgA), immunoglobulin G (IgG) and immunoglobulin M (IgM) were successively increased in severe PIH group, mild-moderate PIH group and normal pregnancy group (P<0.05). Compared with those in normal pregnancy group, the levels of PT, APTT and TT were significantly decreased and Fib levels were significantly increased in PIH groups (P<0.05). Compared with those in normal pregnant women, the levels of TNF-α and IL-6 in pregnant women with PIH were significantly increased (P<0.05), and the changes in severe PIH group were more obvious than those in mild-moderate group. Conclusion: Pregnant women with PIH are in a hypercoagulable state and have a higher risk of thrombus and secondary hyperfibrinolysis. Immune factors and inflammatory factors are also associated with the occurrence and development of the disease. Monitoring the changes in coagulation indexes and levels of immune factors and inflammatory factors provide an important reference value for clinical treatment and prevention of complications.